Stress Coping Mediates Between Social Support and Religiosity Against Family Resilience in Driver Travel Agents in Sanur - I Wayan Eka Sudarmawan; Miko Andi Wardana; I Made Hadi Purnantara (Enrichment : Journal of Management, 2022)
Since Covid 19 was declared a pandemic by WHO (World Health Organization) throughout the world, the closure of international airports has been carried out in various countries including Indonesia. This triggered the collapse of the Indonesian tourism sector. As a result of this, many Travel agents were closed resulting in employees and Travel agent drivers losing their jobs. Apart from losing a job, of course it will also affect the financial condition of travel agent drivers, especially in Sanur. The sampling technique used was purposive sampling involving 50 travel agent drivers in Sanur. This study aims to analyze coping stress mediating between social support and religiosity on family resilience. Data analysis was performed using PLS-based SEM. the results of the study show that there is no direct relationship between social support and religiosity on family resilience. In this case coping stress becomes a mediating variable between social support and religiosity on family resilience.